Colony Forming Bacterial Count in Dental Unit Water Lines of Rehman College of Dentistry, Peshawar - Wahaj Anees, Moiz Ahmed Shaikh, Munir Hussain Zardari, Lubna M Arif, Hans Kumar, Ather Akber (Pakistan Journal of Medical & Health Sciences, 2022)
Bacterial invasion of dental unit water lines is a global issue, which if left untreated, leads to formation of a bacterial biofilm within the water lines. The aim of this study was to determine the number of colony forming units (CFU) in dental unit waterlines of Rehman college of dentistry. Samples from air-water syringes of 44 different dental units in various departments of the dental hospital were collected. Tip of each air-water syringe was heated using direct flaming to eliminate any bacteria residing therein. The samples were collected in 100ml sterile bottles and labelled according to the unit number and department name. The bottles were sent for bacteriological analysis to public health food analysis laboratory, Peshawar. The results concluded that according to the WHO standards of water contamination, all samples fall in category B (1-10cfu/ml) and were deemed fit for drinking. Keywords: Colony forming units, dental unit water lines (DUWL), dental unit water system (DUWS), Peshawar, Pakistan, bacterial load.